Epithelial tumors: Growing from within. Issue 2 (3rd April 2018) - Muzzopappa, Mariana; Milán, Marco
ABSTRACT: The growth of epithelial tumors is often governed by cell interactions with the surrounding stroma. Drosophila has been instrumental in identifying the relevant molecular elements mediating these interactions. Of note is the role of the TNF ligand Eiger, released from recruited blood cells, in activating the JNK tumor-promoting pathway in epithelial tumors. JNK drives the transcriptional induction of mitogenic molecules, matrix metalloproteases and systemic signals that lead to tumor growth, tissue invasiveness and malignancy. Here we review our findings on a tumor-intrinsic, Eiger- and stroma-independent mechanism that contributes to the unlimited growth potential of tumors caused either by chromosomal instability or impaired cell polarity. This newly identified mechanism, which was revealed in an experimental condition in which contacts between tumor cells and wild-type epithelial cells were minimized, relies on interactions between functionally distinct tumor cell populations that activate JNK in a cell-autonomous manner. We discuss the impact of cell interaction-based feedback amplification loops on the unlimited growth potential of epithelial tumors. These findings are expected to contribute to the identification of the relevant cell populations and molecular mechanisms to be targeted in drug therapy.